Banking and commerce: A liquidity approach - Haubrich, Joseph G.; Santos, João A.C. (Journal of Banking & Finance, 2005)
This paper looks at the advantages and disadvantages of mixing banking and commerce, using the “liquidity” approach to financial intermediation. Bringing a nonfinancial firm into a banking conglomerate may be advantageous because it makes it easier for the bank to dispose of assets seized in a loan default. The conglomerate's internal market increases the liquidity of such assets and improves the bank's ability to perform financial intermediation. More generally, owning a nonfinancial firm may act either as a substitute or a complement to commercial lending. In some cases, a bank will voluntarily refrain from making loans, choosing to become a non-bank bank in an unregulated environment.